Institutional Factors Affecting Foreign Direct Investment and Bilateral Investment Treaties - Mostafa Heidari Haratemeh (پژوهش‌های برنامه و توسعه)
The present study attempts to investigate the institutional factors affecting bilateral or multilateral investment treaties with regard to foreign direct investment. This is an applied research based on descriptive and correlational approach. In order to test the postulated hypotheses, given the availability of data, 42 countries were considered for the period 2006-2021, and the PPML technique was applied using Eviews 13 within the framework of the gravity model. The results showed that investment treaties have a positive and significant effect on foreign direct investment, although this effect will be greater in the case of developing countries. Factors such as common language, market capacity, and distance also have a significant impact, whereas population and geographic proximity are not significant determinants for the flow of foreign direct investment except for the paired developing countries. In general, the empirical investigation demonstrated that a bilateral investment treaty acts as a signaling device, indicating that the host country is serious about protecting the investment.